The EU framework for social innovation - Between entrepreneurship and policy experimentation - ImPRovE, Antwerp; Sabato, Sebastiano; Vanhercke, Bart; Verschraegen, Gert (Antwerp, 2015)
"The aim of this paper is to identify and provide a preliminary assessment of the resources that the EU has made available to promote social innovation over the period 2006-2014, with special focus on poverty and social exclusion policies. Such a focus is relevant insofar as the establishment of a quantitative target concerning poverty and social exclusion has been one of the major novelties introduced by the Europe 2020 Strategy: social innovation has been presented as a key area for facilitating its achievement. In order to identify European Union (EU) resources relevant for social innovation, we have adopted a diachronic approach taking into account two sub-periods: 2006-2010 (the period of the revised Lisbon Strategy) and 2010-2014 (the first stage of the new Europe 2020 Strategy). This has allowed us to shed light on both the varying importance of the issue over time and the evolution of the relevant instruments and processes implemented by the EU. Our analysis also provides insights into the complex and multi-layered European policy architecture for underpinning social innovation.(for more see paper)"